Analysis of the Development of Elementary School Students' Financial Literacy - Cholifah Tur Rosidah; Apri Irianto; Bahauddin Azmy; Marella Vintya Christi; Anis Cahyaningtyas; Ismi Mazidah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to analyze the development of students' financial literacy skills during the period 2019-2024. Financial literacy, which includes an understanding of money management, investment, and financial planning, is an essential competency in equipping students to face global economic challenges. This study uses a qualitative approach with descriptive methods, combining in-depth interviews, participant observation, and document analysis to explore students' financial understanding, attitudes, and practices. Data were collected from elementary school students in various regions to ensure diversity in social, economic, and cultural backgrounds. Data analysis was carried out thematically by identifying key patterns related to financial literacy skills, influencing factors, and changes that have occurred over the past five years. The results of the study show an increase in students' awareness of the importance of financial literacy, especially after the integration of financial literacy into the national education curriculum and the massive influence of digital financial technology. However, challenges such as gaps in access to information, low parental participation, and lack of practical training in financial management are still major obstacles. This study suggests increasing collaboration between schools, families, and communities in providing comprehensive and applicable financial literacy education. These findings provide insights for educators, policymakers, and financial institutions to design more effective strategies to improve students' financial literacy skills in the future.